Differentiation of black teas by volatile profile analysis using HS-SPME/GC-MS - Tuan, Hoang Q.; Thinh, Nguyen D.; M. Tu, Nguyen T. (Vietnam Journal of Science and Technology, 2016)
A total of fourteen different commercial brands of black teas including Orthodox (OTD) teas and Crush Tear Curl (CTC) teas were collected at different markets with origin from 07 countries, and their volatile flavour compounds (VFC) were compared by analyses, using headspace solid-phase micro-extraction coupled with gas chromatograph mass spectrometry (HS-SPME/GC-MS). Among the 60 volatiles identified, terpenes (10.28%-59.88% PAR), ketones (1.85%-22.02% PAR) and esters (3.13%-418% PAR) represented the most abundant compounds. The result showed that the number of volatile compounds detected in the aromas of CTC teas were lower than in orthodox tea. Furthermore, the low contents of aldehydes and alcohols in the volatile profile of CTC tea in comparison with OTD tea, while the content of esters in the CTC teas is higher than those of OTD teas were found. Both teas, Orthodox tea and CTC tea, could be classified base on volatile profiles analysis by carrying out principal component analysis (PCA) and cluster analysis. The data presented in this studied also suggest that, for <a href="http://www.google.com.vn/url?sa=t&rct=j&q=&esrc=s&source=web&cd=1&cad=rja&ved=0CDcQFjAA&url=http%3A%2F%2Flink.springer.com%2Farticle%2F10.1007%252Fs12161-011-9319-9&ei=s94pUsO6L-TkiAehvoEI&usg=AFQjCNH8UlYx8KwSsQ8mVsk1FarusvQwWQ&bvm=bv.51773540,d.aGc">geographical origin of teas, Terpene Index can be used as a means of discrimination.